Methacrylic based copolymer, composition, molding, film, method for manufacturing sheet, and laminate
Patent Information
- Application Number
- JP2024211691
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0019】 本発明によれば、耐熱性に優れるとともに、配向複屈折と光弾性複屈折がともに小さく、表面硬度が高いメタクリル系共重合体、および前記共重合体を含む組成物、成形体、フィルム又はシートの製造方法、積層体を得ることができる。
Smart Images

Figure 2025026525000001 
Figure 2025026525000002 
Figure 2025026525000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a methacrylic copolymer, a composition, a molded article, a method for producing a film or sheet, and a laminate. [Background technology]
[0002] (Meth)acrylic resins are widely used as materials for optical components such as lenses, prisms, retardation films, light guide plates, light diffusion films, and polarizing plate protective films, due to their excellent transparency and low optical distortion. In these applications, the birefringence of the molded products affects the performance of the devices. For example, in devices such as liquid crystal display devices, optical disk devices, and projection screens, the presence of films, lenses, etc. with birefringence in the optical path adversely affects image quality and signal reading performance. For this reason, in recent years, there has been a demand for materials with birefringence as small as possible.
[0003] The birefringence exhibited by a resin includes orientation birefringence caused by the orientation of polymer molecules and photoelastic birefringence caused by stress, which are inherent properties of the polymer derived from the primary structure of the polymer.
[0004] In the repeating unit of a general polymer, the polarizability in the main chain direction and the side chain direction are different, and the polarizability is anisotropic. When no strain is applied to the polymer, the repeating units are randomly oriented, so the anisotropy of the repeating units cancels each other out, and the macroscopic refractive index becomes isotropic. However, in a process of molding a general polymer, such as the extrusion molding or stretching process in the production of a polymer film, or the injection molding process that is often used in the production of various optical components, which involves the flow of materials, the orientation of the polymer main chain occurs, and the orientation is fixed and remains in the optical component. In a state in which the main chain is oriented, the macroscopic isotropy is broken, and the polarizability anisotropy derived from the repeating unit of the polymer is expressed in the optical component depending on the degree of orientation of the main chain. Such birefringence caused by the orientation of the polymer main chain is called orientation birefringence. Here, when the refractive index increases in the direction parallel to the orientation direction of the main chain, it is expressed as positive orientation birefringence, and when the refractive index increases in the perpendicular direction, it is expressed as negative orientation birefringence.
[0005] It is also known that birefringence occurs when a polymer undergoes elastic deformation, and this is called photoelastic birefringence. For example, when an optical component containing a polymer is fixed to an apparatus and receives an external force and undergoes elastic deformation, it will exhibit photoelastic birefringence according to the photoelastic coefficient. In addition, when an optical component is molded, residual strain in the material due to volume shrinkage during cooling from a molding temperature above the glass transition temperature of the polymer can also cause photoelastic birefringence.
[0006] Various attempts have been made to simultaneously reduce the orientation birefringence and the photoelastic birefringence and to suppress the birefringence of a polymer.
[0007] As a method for obtaining a low birefringence material, a technique is known in which a plurality of monomers having different signs of intrinsic birefringence and photoelastic coefficient as homopolymers are combined and copolymerized by adjusting the composition so that the intrinsic birefringence and photoelastic coefficient are offset, thereby reducing the orientation birefringence and photoelastic birefringence as a copolymer. For example, Patent Document 1 discloses that a copolymer containing methyl methacrylate units, 2,2,2-trifluoroethyl methacrylate units, and benzyl methacrylate units can simultaneously reduce the orientation birefringence and photoelastic birefringence. However, the resin has a low glass transition temperature, which results in poor heat resistance, limiting its application to electronic devices and in-vehicle applications that are expected to be used under high temperature conditions.
[0008] Therefore, as a resin that has heat resistance and reduced birefringence, a (meth)acrylic resin containing glutarimide units has been proposed in Patent Document 2. However, although this resin has low orientation birefringence, it does not have sufficient reduced photoelastic birefringence, and therefore there is a problem in that birefringence appears due to residual strain in the molded product or stress applied when the optical member is mounted on a device.
[0009] In response to these demands, as resins that have heat resistance and reduce both orientation birefringence and photoelastic birefringence, acrylic thermoplastic resins containing methacrylate monomer units, vinyl aromatic monomer units, methacrylate monomer units having aromatic groups, and cyclic acid anhydride repeating units (Patent Document 3), and imide resins containing N-substituted or unsubstituted glutarimide units, (meth)acrylic acid ester monomer units, and vinyl aromatic monomer units (Patent Document 4) have been disclosed. However, according to the authors' investigation, the resins in Patent Documents 3 and 4 have insufficient surface hardness, and there are still problems to be solved in applying them as optical members. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2006-308682 A [Patent Document 2] JP 2006-328330 A [Patent Document 3] WO2009 / 084541 A1 [Patent Document 4] WO2005 / 054311 A1 Summary of the Invention [Problem to be solved by the invention]
[0011] The object of the present invention is to provide a methacrylic copolymer which has excellent heat resistance, small orientation birefringence and photoelastic birefringence, and high surface hardness, and a method for producing a composition, molded article, film or sheet, and laminate containing the copolymer. [Means for solving the problem]
[0012] As a result of intensive research conducted in order to achieve the above object, the present invention has been completed, which includes the following aspects. [1] The polymer contains a structural unit (R) having at least one ring structure selected from the group consisting of methyl methacrylate units, α-methylstyrene units, maleic anhydride units, and the following formulas (1) to (3) in its main chain, and has an absolute photoelastic coefficient of 3.0×10 -12 Pa -1 The absolute value of orientation birefringence of a stretched film obtained by stretching a 20 mm × 40 mm × 1.0 mm sheet in one direction by 100% at a speed of 3 mm / min at a temperature 10° C. higher than the glass transition temperature is 2.5×10 -4 The following is a methacrylic copolymer:
[0013] [ka]
[0014] (In formula (1), R 11 and R 12 are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.
[0015] [ka]
[0016] (In formula (2), R 21 and R 22 are each independently a hydrogen atom or a methyl group, R 23 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.
[0017] [ka]
[0018] (In formula (3), R 31 and R 32 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms; R 33 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. [2] The methacrylic copolymer according to [1], wherein the structural unit (R) is at least one structural unit selected from the group consisting of an N-substituted or unsubstituted glutarimide unit represented by formula (2) or an N-substituted or unsubstituted maleimide unit represented by formula (3). [3] The methacrylic copolymer according to [1] or [2], having a glass transition temperature of 120° C. or higher. [4] The methacrylic copolymer according to any one of [1] to [3], containing 22 to 87 mass% of methyl methacrylate units, 7 to 30 mass% of α-methylstyrene units, 1 to 30 mass% of maleic anhydride units, and 3 to 70 mass% of structural units (R). [5] A resin composition comprising the methacrylic copolymer according to any one of [1] to [4]. [6] A molded article comprising the methacrylic copolymer according to any one of [1] to [4] or the composition according to [5]. [7] The molded article according to [6], wherein the molded article is a film or a sheet. [8] A method for producing a film or sheet, comprising a step of forming the methacrylic copolymer according to any one of [1] to [4] or the composition according to [5] into a film or sheet by a melt molding method. [9] A method for producing a film or sheet, comprising a step of forming the methacrylic copolymer according to any one of [1] to [4] or the composition according to [5] into a film or sheet by a solution casting method.
[10] A laminate having at least one layer made of a film or sheet containing the methacrylic copolymer according to any one of [1] to [4] or the composition according to [5]. Effect of the Invention
[0019] According to the present invention, it is possible to obtain a methacrylic copolymer which has excellent heat resistance, small orientation birefringence and photoelastic birefringence, and high surface hardness, as well as a composition, a molded product, a film or sheet manufacturing method, and a laminate containing the copolymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] (Methacrylic copolymer) The methacrylic copolymer of the present invention contains methyl methacrylate units, α-methylstyrene units, maleic anhydride units, and structural units (R).
[0021] In the methacrylic copolymer of the present invention, the proportion of methyl methacrylate units is preferably 22 to 87% by mass, more preferably 27 to 85% by mass, and further preferably 32 to 80% by mass, based on the total structural units. If the proportion of methyl methacrylate units is less than this range, the total light transmittance of the resulting methacrylic copolymer is deteriorated, whereas if the proportion of methyl methacrylate units is more than this range, the heat resistance of the resulting methacrylic copolymer is reduced.
[0022] In the methacrylic copolymer of the present invention, the ratio of α-methylstyrene units is preferably 7 to 30 mass%, more preferably 8 to 27 mass%, and further preferably 11 to 25 mass% based on the total structural units. If the ratio of α-methylstyrene units is less than this range, the surface hardness of the resulting methacrylic copolymer is low. If the ratio of α-methylstyrene units is more than this range, the polymerizability of the resulting methacrylic copolymer is low, and the productivity is reduced.
[0023]
[0024] The structural unit (R) is a structural unit having at least one ring structure in the main chain selected from the group consisting of a glutaric anhydride unit, an N-substituted or unsubstituted glutarimide unit, and an N-substituted or unsubstituted maleimide unit.
[0025] The glutaric anhydride unit is a unit having a 2,6-dioxodihydropyrandiyl structure. An example of the unit having a 2,6-dioxodihydropyrandiyl structure is a structural unit represented by the formula (1).
[0026] [ka]
[0027] In formula (1), R 11 and R 12 each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and is preferably a methyl group.
[0028] The unit having a 2,6-dioxodihydropyrandiyl structure can be incorporated into the methacrylic copolymer by the method described in JP 2007-197703 A, JP 2010-96919 A, or the like, for example, by intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid, or intramolecular cyclization of a structural unit derived from (meth)acrylic acid and a structural unit derived from methyl (meth)acrylate.
[0029] The N-substituted or unsubstituted glutarimide unit is a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure.
[0030] An example of a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure is a structural unit represented by formula (2).
[0031] [ka]
[0032] In formula (2), R 21 and R 22 R is independently a hydrogen atom or a methyl group, and is preferably a methyl group. 23 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group containing an aromatic ring and having 6 to 15 carbon atoms, preferably a hydrogen atom, a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, and more preferably a methyl group, an n-butyl group, or a cyclohexyl group.
[0033] The structural unit represented by formula (2) can be prepared by, for example, reacting the corresponding acid anhydride (1a) with R 23 It may be produced by a reaction of an imidizing agent represented by -NH2, or by an intramolecular cyclization reaction of a copolymer having a partial structure represented by formula (4). It is preferable to heat the copolymer to convert the structural unit represented by formula (4) to the structural unit represented by formula (2) by the intramolecular cyclization reaction. Scheme (i)
[0034] [ka]
[0035] (In the formula, R 21 , R 22 , R 23 is as defined above.) The N-substituted or unsubstituted glutarimide unit can be obtained by the method described in WO2005 / 10838A1, JP2010-254742A, JP2008-273140A, JP2008-274187A, etc., specifically, by reacting a structural unit derived from two adjacent methyl methacrylates or a glutaric anhydride unit with an imidizing agent such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, etc., an aromatic hydrocarbon group-containing amine such as aniline, toluidine, trichloroaniline, etc., an alicyclic hydrocarbon group-containing amine such as cyclohexylamine, etc., urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, etc. Among these, methylamine is preferred.
[0036] The N-substituted or unsubstituted maleimide unit is a unit having an N-substituted or unsubstituted 2,5-dioxo-2,5-dihydropyrrole-3,4-diyl structure.
[0037] An example of a unit having an N-substituted or unsubstituted 2,5-dioxo-2,5-dihydropyrrole-3,4-diyl structure is a structural unit represented by formula (3).
[0038] [ka]
[0039] In formula (3), R 31 and R 32are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms; R 33 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.
[0040] The method for forming the N-substituted or unsubstituted maleimide unit is not particularly limited, and the N-substituted or unsubstituted maleimide unit may be formed by copolymerizing a corresponding N-substituted or unsubstituted maleimide monomer. Examples of the N-substituted or unsubstituted maleimide monomer include maleimide; N-methylmaleimide, N-ethylmaleimide, Nn-propylmaleimide, N-isopropylmaleimide, Nn-butylmaleimide, N-isobutylmaleimide, Ns-butylmaleimide, Nt-butylmaleimide, Nn-pentylmaleimide, Nn-hexylmaleimide, Nn-heptylmaleimide, Nn-octylmaleimide, N-laurylmaleimide, N-stearylmaleimide, and the like. N-alkylmaleimides such as imides; N-cyclopentylmaleimide, N-cyclohexylmaleimide, 1-cyclohexyl-3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-diphenyl-1H-pyrrole-2,5-dione, etc. Chloroalkylmaleimide; N-phenylmaleimide, N-(2-chlorophenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, N-(2-methylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-(2-nitrophenyl)maleimide, N-(2,4,6-trimethylphenyl)maleimide, N-(4-benzylphenyl)maleimide N-arylmaleimides such as N-(2,4,6-tribromophenyl)maleimide, N-naphthylmaleimide, N-anthracenylmaleimide, 3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1,3-diphenyl-1H-pyrrole-2,5-dione, and 1,3,4-triphenyl-1H-pyrrole-2,5-dione; and N-benzylmaleimide.Among these monomers, from the viewpoint of weather resistance of the methacrylic copolymer, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, N-cyclohexylmaleimide, N-phenylmaleimide, and N-benzylmaleimide are preferred, and N-methylmaleimide, N-cyclohexylmaleimide, and N-phenylmaleimide are particularly preferred.
[0041] The N-substituted or unsubstituted maleimide unit can also be obtained by the method described in JP-A-2006-124592, specifically by reacting a maleic anhydride unit with an imidizing agent. Examples of the imidizing agent include ammonia, aliphatic hydrocarbon group-containing amines such as methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, and n-hexylamine, aromatic hydrocarbon group-containing amines such as aniline, toluidine, trichloroaniline, and benzylamine, alicyclic hydrocarbon group-containing amines such as cyclohexylamine, urea, 1,3-dimethylurea, 1,3-diethylurea, and 1,3-dipropylurea, and among these imidizing agents, methylamine is preferred.
[0042] In the methacrylic copolymer of the present invention, the ratio of the structural unit (R) to the total structural units is preferably 3 to 70 mass%, more preferably 5 to 65 mass%, and further preferably 8 to 60 mass%. If the ratio of the structural unit (R) to the total structural units is within the above range, it is preferable because a methacrylic copolymer having high heat resistance and excellent moldability can be obtained while suitably controlling the birefringence of the resin.
[0043] The methacrylic copolymer of the present invention may contain other copolymerizable vinyl monomer units in addition to the methyl methacrylate unit, the α-methylstyrene unit, the maleic anhydride unit, and the structural unit (R). Examples of the copolymerizable vinyl monomers include methacrylic acid alkyl esters other than methyl methacrylate, such as ethyl methacrylate and butyl methacrylate; methacrylic acid aryl esters such as phenyl methacrylate; methacrylic acid cycloalkyl esters such as cyclohexyl methacrylate and norbornenyl methacrylate; acrylic acid alkyl esters such as methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate; acrylic acid aryl esters such as phenyl acrylate; acrylic acid cycloalkyl esters such as cyclohexyl acrylate and norbornenyl acrylate; aromatic vinyl monomers other than α-methylstyrene, such as styrene; acrylamide; methacrylamide; cyanide vinyl monomers such as acrylonitrile and methacrylonitrile; and vinyl monomers having only one polymerizable alkenyl group in one molecule. Of these monomers, from the viewpoint of highly controlling the birefringence of the methacrylic copolymer, preferred are acrylic acid alkyl esters, aromatic vinyl monomers other than α-methylstyrene, and vinyl cyanide monomers, more preferred are methyl acrylate, styrene, and acrylonitrile, and even more preferred is styrene.
[0044] In the methacrylic copolymer of the present invention, the proportion of other copolymerizable vinyl monomer units is preferably 30 mass % or less based on the total structural units.
[0045] The methacrylic copolymer of the present invention has a weight average molecular weight (Mw) of preferably 40,000 to 200,000, more preferably 50,000 to 180,000, and further preferably 55,000 to 160,000. When Mw is 40,000 or more, the strength, toughness, etc. of the molded article of the present invention are improved. When Mw is 200,000 or less, the flowability of the methacrylic copolymer of the present invention is improved, and molding processability is improved.
[0046] The weight average molecular weight (Mw) is a value calculated by converting a chromatogram measured by gel permeation chromatography (GPC) into the molecular weight of standard polystyrene.
[0047] The methacrylic copolymer of the present invention has an acid value of preferably 0.01 to 0.30 mmol / g, more preferably 0.05 to 0.28 mmol / g. The acid value is a value proportional to the content of carboxylic acid units and carboxylic anhydride units in the methacrylic copolymer. The acid value can be calculated, for example, by the method described in JP-A-2005-23272. When the acid value is within the above range, the balance of heat resistance, mechanical properties, and moldability is excellent.
[0048] The methacrylic copolymer of the present invention has a glass transition temperature of preferably 120° C., more preferably 121° C., and further preferably 122° C. as a lower limit, and preferably 200° C. as an upper limit, although not particularly limited. The higher the glass transition temperature of the methacrylic copolymer, the less likely a molded article containing the methacrylic copolymer is to deform or shrink due to heat, i.e., the higher the heat resistance.
[0049] In this specification, the "glass transition temperature (Tg)" is measured in accordance with JIS K7121. Specifically, the temperature is raised once to 230°C, then cooled to room temperature, and then the DSC curve is measured under conditions of raising the temperature from room temperature to 230°C at a rate of 10°C / min. The midpoint determined from the DSC curve measured during the second heating is determined as the "glass transition temperature (Tg)".
[0050] The methacrylic copolymer of the present invention has an absolute photoelastic coefficient of 3.0×10 -12 Pa -1 It is preferably 2.5×10 or less. More preferably, it is 2.5×10 -12 Pa -1 More preferably, 2.0×10 -12 Pa -1 The following is the result.
[0051] The photoelastic coefficient was measured by applying tension to a press-molded sheet of methacrylic copolymer, 15 mm wide x 60 mm long x 1.0 mm thick, at a chuck distance of 45 mm and a temperature of 23°C, increasing the tension from 0 N to 100 N in increments of 10 N. Each time the tension was increased, the birefringence of the central part of the sheet was measured at a temperature of 23°C and the D-line wavelength of Na, and the slope was calculated by approximating the relationship between the measured stress and birefringence to a linear function using the least squares method. The stress is the value obtained by dividing the tension by the cross-sectional area of the sheet. The cross-sectional area of the sheet was calculated as the product of the sheet width of 15 mm and the thickness at the measurement point in the central part of the sheet. Birefringence is the refractive index n p and the refractive index n of light with a polarization plane perpendicular to the tensile direction o Difference from (Δn=n p -n o )
[0052] The methacrylic copolymer of the present invention has an absolute value of orientation birefringence of 2.5×10 -4 It is preferably 2.3×10 or less. More preferably, it is 2.3×10 -4 More preferably, 2.2×10 -4 More preferably, 2.0×10 -4 The following is the result.
[0053] The orientation birefringence is the birefringence measured at the center of a stretched film obtained by stretching a press-molded sheet made of a methacrylic copolymer, measuring 20 mm in width, 40 mm in length, and 1.0 mm in thickness, in one direction by 100% at a temperature 10°C higher than the glass transition temperature at a speed of 3 mm / min, at a temperature of 23°C and at a Na D-line wavelength, without applying tension. (Methacrylic copolymer manufacturing method) The methacrylic copolymer of the present invention can be obtained, for example, by a method including subjecting a copolymer (hereinafter sometimes referred to as a precursor polymer) of methyl methacrylate, α-methylstyrene, maleic anhydride, and any other copolymerizable vinyl monomer selected therefrom to a ring structure-forming reaction.
[0054] That is, the method for producing the methacrylic copolymer of the present invention comprises the steps of continuously supplying a monomer mixture containing 51 to 94 mass % of methyl methacrylate, 5 to 30 mass % of α-methylstyrene, 1 to 30 mass % of maleic anhydride, and 0 to 30 mass % of other copolymerizable vinyl monomers, a radical polymerization initiator, and optionally a chain transfer agent, to a tank-type reactor; A step of bulk polymerizing the monomer mixture in a tank reactor to a polymerization conversion rate of 30 to 60 mass % to obtain a reaction product; and removing the monomer mixture in the reaction product to obtain a precursor polymer; A step of subjecting the obtained precursor polymer to a ring structure forming reaction. Each step can be carried out by a known technique.
[0055] The precursor polymer is produced by polymerization of reaction raw materials including a monomer mixture, a radical polymerization initiator, and optionally a chain transfer agent, and the monomer mixture contains 51 to 94 mass%, preferably 55 to 85 mass%, of methyl methacrylate in the monomer mixture. The monomer mixture contains 5 to 30 mass%, preferably 7 to 25 mass%, of α-methylstyrene. The monomer mixture contains 1 to 30 mass%, preferably 3 to 25 mass%, of maleic anhydride. The monomer mixture contains 0 to 30 mass%, preferably 3 to 25 mass%, of other copolymerizable vinyl monomers.
[0056] The monomer mixture may contain other copolymerizable vinyl monomers other than methyl methacrylate, α-methylstyrene, and maleic anhydride. Specific examples thereof include the monomers exemplified above, and preferred examples are also the same.
[0057] The monomer mixture preferably has b* of -1 to 2, more preferably -0.5 to 1.5. When b* is in this range, it is advantageous in obtaining molded products with little coloring at high production efficiency when the resulting methacrylic copolymer composition is molded. Note that b* is a value measured in accordance with the International Commission on Illumination (CIE) standard (1976) or JIS Z-8722.
[0058] The polymerization initiator used is not particularly limited as long as it generates reactive radicals. Examples of the polymerization initiator include peroxide initiators such as diisopropylbenzene hydroperoxide and t-butyl hydroperoxide, and azo initiators such as 2,2'-azobis(2-methylpropionitrile).
[0059] The polymerization initiator used has an average uncleaved initiator concentration of 5.1 × 10 at the polymerization temperature in a tank reactor described below. -5 ~2.4×10 -4 (mol / L) range is desirable.
[0060] The amount of the polymerization initiator used is adjusted to the polymerization temperature and added to the monomer mixture so as to obtain the above-mentioned initiator concentration.
[0061] The chain transfer agent used is preferably a monofunctional alkyl mercaptan such as n-octyl mercaptan or n-dodecyl mercaptan. These chain transfer agents can be used alone or in combination of two or more. The amount of the chain transfer agent used is preferably 0 to 1 part by mass, more preferably 0.01 to 0.8 parts by mass, and even more preferably 0.02 to 0.6 parts by mass, based on 100 parts by mass of the monomer mixture.
[0062] In bulk polymerization, a solvent is not used in principle, but an organic solvent can be included in the reaction raw materials as necessary for the purpose of adjusting the polymerization reaction rate and the viscosity of the reaction liquid. Examples of organic solvents include aromatic hydrocarbons such as benzene, toluene, and xylene, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and acetophenone, and ethers such as tetrahydrofuran and 1,4-dioxane. From the viewpoint of the solubility of monomers and copolymers and the ease of solvent recovery, methyl ethyl ketone, methyl isobutyl ketone, and toluene are preferred. The organic solvents can be used alone or in combination of two or more. The upper limit of the amount of organic solvent used is preferably 30 parts by mass, more preferably 25 parts by mass, and even more preferably 20 parts by mass, relative to 100 parts by mass of the monomer mixture. The lower limit of the amount of organic solvent used is usually 0 parts by mass, preferably 1 part by mass.
[0063] The temperature inside the tank reactor, i.e., the temperature of the liquid inside the reaction tank, is preferably 110 to 140° C., more preferably 114 to 135° C. If the temperature is higher than this range, it becomes difficult to produce high molecular weight compounds containing α-methylstyrene, which causes a decrease in heat resistance.
[0064] In a tank reactor, bulk polymerization is preferably carried out until the polymerization conversion rate reaches 30 to 65% by mass, and more preferably 35 to 60% by mass.
[0065] The average residence time (θ) of the reaction raw materials in the tank reactor is preferably 1.5 to 5 hours, more preferably 2 to 4.5 hours, and even more preferably 2.5 to 4 hours. If the average residence time is too short, the amount of polymerization initiator required increases. Furthermore, an increase in the amount of polymerization initiator makes it difficult to control the polymerization reaction and tends to make it difficult to control the molecular weight. On the other hand, if the average residence time is too long, it takes time for the reaction to reach a steady state, and productivity tends to decrease. The average residence time can be adjusted by the capacity of the tank reactor and the amount of reaction raw materials supplied.
[0066] The bulk polymerization is preferably carried out in an atmosphere of an inert gas such as nitrogen gas.
[0067] A preferred production method according to the present invention includes a step of removing the monomer mixture from the reaction product. The removal method is not particularly limited, but a heat devolatilization method is preferred. After removing the monomer mixture, the methacrylic copolymer composition can be made into pellets or powder according to a known method to facilitate handling as a molding material. The content of the monomer mixture in the resulting methacrylic resin composition is preferably 1% by mass or less, more preferably 0.5% by mass or less.
[0068] The precursor polymer has a glass transition temperature of preferably 114°C, more preferably 115°C, and further preferably 117°C as a lower limit. The glass transition temperature can be changed by adjusting the molecular weight, the amount of α-methylstyrene copolymerized, and the like. The higher the glass transition temperature of the precursor polymer, the more improved the heat resistance. A methacrylic copolymer obtained by using a precursor polymer having a high glass transition temperature has high heat resistance even if the amount of structural unit (R) is small, and is therefore unlikely to cause deterioration of saturated water absorption, etc.
[0069] The precursor polymer is not particularly limited as long as the total content of structural units derived from methyl methacrylate is 51 to 92% by mass, the total content of structural units derived from α-methylstyrene is 5 to 30% by mass, and the total content of structural units derived from maleic anhydride is 1 to 30% by mass. From the viewpoints of polymerizability, transparency, and the like, the total content of structural units derived from methyl methacrylate in the precursor polymer is preferably 51% by mass or more and 92% by mass or less, more preferably 55% by mass or more and 92% by mass or less, and most preferably 60% by mass or more and 92% by mass or less.
[0070] From the viewpoints of heat resistance, polymerizability, water absorption, etc., the total content of structural units derived from α-methylstyrene in the precursor polymer is preferably 7 to 30 mass%, more preferably 8 to 27 mass%, and further preferably 11 to 25 mass%. If the structural units derived from α-methylstyrene are less than this range, sufficient heat resistance cannot be obtained, and if they are more than this range, polymerizability is significantly reduced.
[0071] From the viewpoint of heat resistance and controllability of optical properties (particularly birefringence), the total content of structural units derived from maleic anhydride in the precursor polymer is preferably 1 to 30 mass%, more preferably 2 to 27 mass%, and even more preferably 3 to 27 mass%. If the structural units derived from maleic anhydride are less than this range, the birefringence becomes high, whereas if they are more than this range, the heat resistance and melt viscosity of the precursor polymer unnecessarily increase, decreasing the productivity in the ring structure forming reaction described later.
[0072] The precursor polymer has a polystyrene-equivalent weight average molecular weight Mw of preferably 40,000 to 200,000, more preferably 40,000 to 180,000, and even more preferably 50,000 to 160,000 in a chromatogram obtained by gel permeation chromatography. If the weight average molecular weight Mw is smaller than this range, the resulting molded article becomes brittle, and if it is higher than this range, the productivity deteriorates. Mw can be controlled by adjusting the type, amount, and addition timing of the polymerization initiator and chain transfer agent (optional components) used in the production of the precursor polymer.
[0073] The ring structure forming reaction can be carried out, for example, using an extruder. Examples of the extruder include a single screw extruder, a twin screw extruder, and a multi-screw extruder. From the viewpoint of mixing performance, a twin screw extruder is preferred. Twin screw extruders include non-intermeshing co-rotating type, intermeshing co-rotating type, non-intermeshing counter-rotating type, and intermeshing counter-rotating type. The intermeshing co-rotating type is preferred because it can rotate at high speed and can efficiently promote mixing. These extruders may be used alone or connected in series.
[0074] In the ring structure forming reaction using an extruder, for example, a precursor polymer as a raw material is charged from the raw material charging section of the extruder, the precursor polymer is melted, and the cylinder is filled with the precursor polymer, and then an imidizing agent (optional component) and the like are injected into the extruder using an addition pump, whereby the ring structure forming reaction can be progressed in the extruder. When an imidizing agent is used, the structural unit (R) contains at least one of an N-substituted or unsubstituted glutarimide unit and an N-substituted or unsubstituted maleimide unit, and may contain a lactone ring unit and / or a glutaric anhydride unit as necessary. A preferred imidizing agent is R 23 -NH2(R 23 is as defined above), or R 33 -NH2(R 33 is as defined above). The imidizing agent is preferably used in an amount of 1.6 to 20 parts by mass per 100 parts by mass of the methacrylic copolymer. When the amount of the imidizing agent used is within the above range, the by-production of methacrylic acid amide units can be suppressed. 33 -NH2(R 33 is as defined above), a part of the maleic anhydride units of the precursor polymer is converted into maleimide units (R 31 =R 32 In one embodiment of the present invention, the imidizing agent R 23 -NH2(R 23 is as defined above) to produce a structural unit (R) represented by formula (2), and at the same time, a maleimide unit (R 31 =R 32 =H) is generated, the structural unit (R) includes structural units of formula (2) and formula (3), and R 23 =R 33 It becomes.
[0075] The resin temperature in the reaction zone in the extruder is preferably in the range of 180 to 300°C, more preferably in the range of 200 to 300°C. If the resin temperature in the reaction zone is less than 180°C, the heat resistance of the methacrylic copolymer tends to decrease due to a decrease in the reaction efficiency of the ring structure formation reaction, the by-production of methacrylamide units, etc. If the resin temperature in the reaction zone exceeds 300°C, the resin decomposition becomes significant, and the mechanical strength, such as the tensile breaking strength, of the molded body and film made of the obtained methacrylic copolymer tends to decrease. The reaction zone in the extruder refers to the region between the injection position of the imidizing agent, etc., in the cylinder of the extruder to the resin discharge port (die part).
[0076] By increasing the reaction time in the reaction zone of the extruder, the ring structure forming reaction can be promoted. The reaction time in the reaction zone of the extruder is preferably longer than 10 seconds, and more preferably longer than 30 seconds. If the reaction time is less than 10 seconds, the ring structure forming reaction may hardly proceed.
[0077] The resin pressure in the extruder is preferably in the range of atmospheric pressure to 50 MPa, and more preferably in the range of 1 to 30 MPa. If it is 50 MPa or more, it exceeds the limit of the mechanical pressure resistance of a normal extruder, and a special device is required, which is not preferable from the viewpoint of cost.
[0078] It is preferable to use an extruder having a vent hole that can reduce the pressure to below atmospheric pressure. With such a configuration, unreacted materials, by-products such as methanol, and monomers can be removed, and the breaking strength of a molded article containing the acrylic resin composition of the present invention tends to be improved.
[0079] For the ring structure-forming reaction, a horizontal twin-screw reactor such as Bivolac manufactured by Sumitomo Heavy Industries, Ltd. or a vertical twin-screw stirring tank such as Superblend, which is suitable for high viscosity reaction, can be suitably used instead of an extruder.
[0080] During the ring structure forming reaction, a carboxyl group may be by-produced in the methacrylic copolymer. This carboxyl group may be converted to an ester group by an esterifying agent or a catalyst, if necessary. This can reduce foaming of the resin during the production of an optical film. The ester group varies depending on the esterifying agent and catalyst used, but from the viewpoints of reducing the resin melt viscosity during melt molding, the reactivity of esterification, and the heat resistance of the resin after esterification, it is preferable that the ester group contains a methyl methacrylate unit, and more preferably contains both a methyl methacrylate unit and an ethyl methacrylate unit.
[0081] As the esterifying agent, dimethyl carbonate is preferred from the viewpoints of cost, reactivity, etc.
[0082] The amount of the esterifying agent added can be set, for example, so that the acid value of the methacrylic copolymer becomes a desired value.
[0083] In addition to the esterification agent, a catalyst can be used in combination. The type of catalyst is not particularly limited, but examples thereof include amine compounds such as trimethylamine, triethylamine, monomethyldiethylamine, and dimethylmonoethylamine. Among these, triethylamine is preferred from the viewpoints of cost, reactivity, and the like.
[0084] (Resin composition) Additives generally used in resin compositions may be included within the scope of the present invention. Examples of additives include fillers, antioxidants, heat deterioration inhibitors, ultraviolet absorbers, light stabilizers, lubricants, mold release agents, polymer processing aids, antistatic agents, flame retardants, colorants, dyes, pigments, light diffusing agents, organic dyes, matting agents, impact resistance modifiers, and fluorescent materials. The total amount of such additives other than the filler is preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less.
[0085] Examples of the filler include calcium carbonate, talc, carbon black, titanium oxide, silica, clay, barium sulfate, magnesium carbonate, etc. The amount of the filler that can be contained in the methacrylic copolymer composition of the present invention is preferably 3% by mass or less, more preferably 1.5% by mass or less.
[0086] The antioxidant is effective in preventing the oxidative deterioration of the resin by itself in the presence of oxygen. Examples of the antioxidant include phosphorus-based antioxidants, hindered phenol-based antioxidants, and thioether-based antioxidants. These antioxidants may be used alone or in combination of two or more.
[0087] The heat deterioration inhibitor is capable of preventing the thermal deterioration of a resin by capturing polymer radicals that are generated when the resin is exposed to high heat in a substantially oxygen-free state.
[0088] Examples of the heat deterioration inhibitor include 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-hydroxybenzyl)-4-methylphenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GM) and 2,4-di-tert-amyl-6-(3',5'-di-tert-amyl-2'-hydroxy-α-methylbenzyl)phenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GS).
[0089] An ultraviolet absorber is a compound that has the ability to absorb ultraviolet rays. An ultraviolet absorber is a compound that is said to have the function of converting light energy into heat energy.
[0090] Examples of ultraviolet absorbents include benzophenones, benzotriazoles, triazines, benzoates, salicylates, cyanoacrylates, oxalic anilides, malonic acid esters, and formamidines. These may be used alone or in combination of two or more. Among these, benzotriazoles, triazines, or compounds having a maximum molar absorption coefficient ε at a wavelength of 380 to 450 nm are preferred. max1200dm 3 mol -1 cm -1 Preferred are UV absorbers which are:
[0091] A light stabilizer is a compound that is said to have the function of capturing radicals generated mainly by oxidation due to light. Suitable light stabilizers include hindered amines such as compounds having a 2,2,6,6-tetraalkylpiperidine skeleton.
[0092] Examples of the lubricant include stearic acid, behenic acid, stearamide acid, methylene bisstearamide, hydroxystearic acid triglyceride, paraffin wax, ketone wax, octyl alcohol, and hardened oil.
[0093] Examples of the release agent include higher alcohols such as cetyl alcohol and stearyl alcohol; and higher fatty acid esters of glycerin such as monoglyceride stearate and diglyceride stearate. In the present invention, it is preferable to use higher alcohols and glycerin fatty acid monoesters in combination as the release agent. When higher alcohols and glycerin fatty acid monoesters are used in combination, the ratio is not particularly limited, but the amount of higher alcohols used: the amount of glycerin fatty acid monoester used is preferably 2.5:1 to 3.5:1, more preferably 2.8:1 to 3.2:1, by mass ratio.
[0094] As the polymer processing aid, polymer particles (non-crosslinked rubber particles) having a particle size of 0.05 to 0.5 μm, which can be produced by emulsion polymerization, are usually used. The polymer particles may be single-layer particles made of a polymer with a single composition ratio and a single intrinsic viscosity, or may be multi-layer particles made of two or more polymers with different composition ratios or intrinsic viscosities.
[0095] Examples of the antistatic agent include alkylsulfonates such as sodium heptyl sulfonate, sodium octyl sulfonate, sodium nonyl sulfonate, sodium decyl sulfonate, sodium dodecyl sulfonate, sodium cetyl sulfonate, sodium octadecyl sulfonate, sodium diheptyl sulfonate, potassium heptyl sulfonate, potassium octyl sulfonate, potassium nonyl sulfonate, potassium decyl sulfonate, potassium dodecyl sulfonate, potassium cetyl sulfonate, potassium octadecyl sulfonate, potassium diheptyl sulfonate, lithium heptyl sulfonate, lithium octyl sulfonate, lithium nonyl sulfonate, lithium decyl sulfonate, lithium dodecyl sulfonate, lithium cetyl sulfonate, lithium octadecyl sulfonate, and lithium diheptyl sulfonate.
[0096] Examples of the flame retardant include metal hydrates having a hydroxyl group or crystal water, such as magnesium hydroxide, aluminum hydroxide, hydrated aluminum silicate, hydrated magnesium silicate, and hydrotalcite; phosphate compounds, such as polyamine phosphoric acid esters; and silicon compounds. Of these, preferred are phosphate ester-based flame retardants, such as trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, tricyclohexyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, dimethylethyl phosphate, methyl dibutyl phosphate, ethyl dipropyl phosphate, and hydroxyphenyl diphenyl phosphate.
[0097] Examples of dyes and pigments include red organic pigments such as Para Red, Fire Red, Pyrazolone Red, Thioindigo Red, and Perylene Red; blue organic pigments such as Cyanine Blue and Indanthrene Blue; and green organic pigments such as Cyanine Green and Naphthol Green. One or more of these can be used.
[0098] As the organic dye, a compound having a function of converting ultraviolet light into visible light is preferably used.
[0099] Examples of the light diffusing agent and the matting agent include glass particles, polysiloxane-based crosslinked particles, crosslinked polymer particles, talc, calcium carbonate, and barium sulfate.
[0100] Examples of fluorescent materials include fluorescent pigments, fluorescent dyes, fluorescent white dyes, fluorescent brighteners, and fluorescent bleaches.
[0101] The methacrylic copolymer composition of the present invention is not particularly limited by its production method, and can be produced, for example, by melt-kneading the methacrylic copolymer of the present invention with additives such as an ultraviolet absorber, and other polymers as necessary. The melt-kneading can be carried out using a melt-kneading device such as a kneader-ruder, an extruder, a mixing roll, or a Banbury mixer. The temperature during kneading can be appropriately set depending on the softening temperatures of the methacrylic copolymer and other polymers, and can be set, for example, to 150 to 300°C. The shear rate during kneading can be, for example, 10 to 5000 sec -1 can be set to.
[0102] The methacrylic copolymer composition of the present invention can be made into a form such as pellets in order to enhance convenience in storage, transportation, or molding. (Molded body) The molded article of the present invention includes the methacrylic copolymer or methacrylic copolymer composition of the present invention. The manufacturing method of the molded article of the present invention is not particularly limited. For example, melt molding methods such as the T-die method (lamination method, coextrusion method, etc.), inflation method (coextrusion method, etc.), compression molding method, blow molding method, calendar molding method, vacuum molding method, injection molding method (insert method, two-color method, press method, core-back method, sandwich method, etc.), and solution casting method can be mentioned. Among these, the T-die method, inflation method, injection molding method, and solution casting method are preferred in terms of high productivity, cost, etc. The type of molded article is not limited, but a film (a planar molded article having a thickness of 5 μm to 250 μm) and a sheet (a planar molded article having a thickness of more than 250 μm) are preferred.
[0103] The molded article of the present invention has an average absolute value of the in-plane retardation (Re) of the molded article, expressed as a value per mm of thickness, of preferably 10.0 nm or less, more preferably 6.0 nm or less, even more preferably 5.0 nm or less, and still more preferably 3.0 nm or less.
[0104] The film, which is one form of the molded article of the present invention, can be produced by a solution casting method, a melt casting method, an extrusion molding method, an inflation molding method, a blow molding method, or the like. Among these, the extrusion molding method or the solution casting method is preferred from the viewpoint of obtaining a film having excellent transparency, improved toughness, excellent handling properties, and an excellent balance between toughness, surface hardness, and rigidity. The temperature of the molten resin discharged from the extruder is preferably set to 160 to 270°C, more preferably 220 to 260°C.
[0105] Among the extrusion molding methods, the T-die method is preferred from the viewpoint of obtaining a film with good surface smoothness, good mirror gloss, and low haze. In this T-die method, it is preferable to sandwich the molten resin discharged from the T-die through an extruder, a gear pump, a polymer filter, and a mixer between two or more mirror-finished rolls or mirror-finished belts to form a film. When sandwiching between the mirror-finished rolls or mirror-finished belts, a bank may or may not be formed. The die has an automatic lip opening adjustment function, and the air gap is preferably 100 mm or less.
[0106] The mirror-finished roll or mirror-finished belt is preferably made of metal. As the mirror-finished roll, a metal rigid roll, a metal elastic roll, etc. can be used, and it is preferable to use a combination of a metal elastic roll and a metal rigid roll. In addition, the surface temperatures of both the mirror-finished roll or the mirror-finished belt are preferably 130°C or less. In addition, it is preferable that at least one of the pair of mirror-finished rolls or mirror-finished belts has a surface temperature of 60°C or more. By setting the surface temperature at such a level, the molten resin discharged from the extruder can be cooled at a rate faster than natural cooling, and a film with excellent surface smoothness and low haze can be easily produced. The linear pressure between the pair of rolls or belts is preferably 10 N / mm or more, more preferably 30 N / mm or more. The thickness of the unstretched film obtained by extrusion molding is preferably 10 to 300 μm. The haze of the film at a thickness of 100 μm is preferably 0.7% or less, more preferably 0.5% or less, and even more preferably 0.3% or less.
[0107] The unstretched film obtained as described above may be subjected to a stretching treatment. The stretching treatment increases the mechanical strength, and a film that is less likely to crack can be obtained. The stretching method is not particularly limited, and examples thereof include simultaneous biaxial stretching, sequential biaxial stretching, and tubular stretching. From the viewpoint of obtaining a film that can be uniformly stretched and has high strength, the lower limit of the temperature during stretching is a temperature 10°C higher than the glass transition temperature of the methacrylic copolymer or methacrylic copolymer composition, and the upper limit of the temperature during stretching is a temperature 40°C higher than the glass transition temperature of the methacrylic copolymer or methacrylic copolymer composition. The stretching is usually performed at 100 to 5000% / min. After stretching, a film with little thermal shrinkage can be obtained by heat setting. The thickness of the film after stretching is preferably 10 to 200 μm.
[0108] A functional layer may be provided on the surface of the film, which is one embodiment of the molded article of the present invention. Examples of the functional layer include a hard coat layer, an antiglare layer, an antireflection layer, an antisticking layer, a diffusion layer, an antiglare layer, an antistatic layer, an antifouling layer, and a slippery layer such as a fine particle layer.
[0109] In addition, it is preferable to provide an undercoat layer on at least one side of the film of the present invention in order to improve the adhesive strength with the functional layer or to improve the adhesive strength when laminated with other films via an adhesive or pressure-sensitive adhesive.
[0110] The methacrylic copolymer or methacrylic copolymer composition of the present invention is suitable as a molding material. The molded article of the present invention can be used as a member for various applications. Specific applications include, for example, signboard parts and marking films such as advertising towers, stand signs, side signs, transom signs, and rooftop signs; display parts such as showcases, partitions, and store displays; lighting parts such as fluorescent lamp covers, mood lighting covers, lampshades, light ceilings, light walls, and chandeliers; interior parts such as furniture, pendants, and mirrors; architectural parts such as doors, domes, safety window glass, partitions, staircase wainscoting, balcony wainscoting, and leisure building roofs; transportation-related parts such as aircraft windshields, pilot visors, motorcycle and motorboat windshields, bus shading plates, automobile side visors, rear visors, head wings, headlight covers, automobile interior parts, and automobile exterior parts such as bumpers; audiovisual nameplates, stereo covers, tapes, etc. Examples of applications include electronic equipment parts such as Levi's protective masks, vending machines, mobile phones, and personal computers; medical equipment parts such as incubators and X-ray parts; equipment-related parts such as machine covers, instrument covers, experimental equipment, rulers, dials, and observation windows; optical parts such as liquid crystal protection plates, light guide plates, light guide films, Fresnel lenses, lenticular lenses, front panels of various displays, and diffusion plates; traffic-related parts such as road signs, information boards, curved mirrors, and soundproof walls; and other parts for greenhouses, large aquariums, box aquariums, bathroom components, clock panels, bathtubs, sanitary products, desk mats, game parts, toys, musical instruments, face protection masks during welding, back sheets for solar cells, front sheets for flexible solar cells, and decorative films.
[0111] A laminate can be obtained by laminating a layer containing the methacrylic copolymer or methacrylic copolymer composition of the present invention with other materials (e.g., a layer containing other thermoplastic copolymers). Examples of other materials used in the laminate include steel, plastics (e.g., thermoplastic resins), wood, glass, etc. The laminate obtained by the present invention can be suitably used for wallpaper; automobile interior surface; automobile exterior surface such as bumpers; mobile phone surface; furniture surface; personal computer surface; vending machine surface; bathroom surface such as bathtub.
[0112] The film, which is one embodiment of the molded article of the present invention, is highly transparent and heat resistant, and therefore suitable for optical applications, and is particularly suitable for polarizer protection films, liquid crystal protection plates, surface materials for portable information terminals, display window protection films for portable information terminals, light guiding films, transparent conductive films with silver nanowires or carbon nanotubes applied to the surface, and front panels for various displays. The film of the present invention has high transparency and heat resistance, and can be used for applications other than optical applications, such as infrared cut films, crime prevention films, shatterproof films, decorative films, metal decorative films, shrink films, and in-mold label films.
[0113] When the film, which is one embodiment of the molded article of the present invention, is used as a polarizer protective film or a retardation film, it may be laminated on only one side of the polarizer film or on both sides. When laminating with the polarizer film, it can be laminated via an adhesive layer or a pressure-sensitive adhesive layer. As the polarizer film, a stretched film made of a polyvinyl alcohol resin and iodine can be used, and its thickness is preferably 1 to 100 μm. EXAMPLES
[0114] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0115] Measurements of physical properties were carried out by the following methods. (Polymerization conversion rate) A gas chromatograph GC-14A manufactured by Shimadzu Corporation was connected to an INERTCAP1 (df=0.4 μm, 0.25 mm I.D.×60 m) manufactured by GL Sciences Inc. as a column, and analysis was performed under the following conditions, and calculations were made based on the results.
[0116] injection temperature=250℃ detector temperature=250℃ Temperature conditions: Hold at 60°C for 5 minutes → Raise temperature to 250°C at 10°C / min → Hold at 250°C for 10 minutes
[0117] (molecular weight) The weight average molecular weight (Mw) of the resin was determined by the GPC method (gel permeation chromatography method). A sample solution was prepared by dissolving 4 mg of the resin to be measured in 5 ml of tetrahydrofuran. The temperature of the column oven was set to 40°C, and 20 μl of the sample solution was injected into the device at an eluent flow rate of 0.35 ml / min to measure the chromatogram. Ten standard polystyrene points with molecular weights in the range of 400 to 5,000,000 were measured by GPC, and a calibration curve showing the relationship between retention time and molecular weight was created. The Mw of the resin to be measured was determined based on this calibration curve.
[0118] Equipment: Tosoh GPC equipment HLC-8320 Separation column: TSKguardcoIumSuperHZ-H, TSKgelHZM-M, and TSKgelSuperHZ4000 manufactured by Tosoh Corporation connected in series Eluent: Tetrahydrofuran Eluent flow rate: 0.35 ml / min Column temperature: 40℃ Detection method: Refractive index (RI)
[0119] (Composition of each unit in the precursor polymer) Inverse Gate Decoupling Method 13The integral ratios of the carbonyl carbon of the methyl methacrylate unit, the aromatic carbon at position 1 of the α-methylstyrene unit, the aromatic carbon at position 1 of the styrene unit, and the carbonyl carbon of the maleic anhydride unit were determined by C-NMR, and the composition of each unit in the precursor polymer was calculated from this.
[0120] (glass transition temperature Tg) The methacrylic copolymers obtained in the Production Examples and Examples were measured for their DSC curves in accordance with JIS K7121 using a differential scanning calorimeter (Shimadzu Corporation, DSC-50 (product number)) by heating them once to 250° C., then cooling them to room temperature, and then heating them from room temperature to 230° C. at a rate of 10° C. / min. The midpoint glass transition temperature determined from the DSC curve measured during the second heating was taken as the glass transition temperature in the present invention.
[0121] (Imidization rate) 1 The copolymer was analyzed using H-NMR (Bruker Corporation; product name ULTRA SHIELD 400 PLUS). 1 H-NMR measurement was performed, and the imidization rate (Im) was calculated using the following formula from the area A of the peak derived from the O-CH3 group of methyl methacrylate around 3.5 to 3.8 ppm and the area B of the peak derived from the N-CH3 group of glutarimide and maleimide around 3.0 to 3.3 ppm. Imidization rate (R) (%) = [B / (A+B)] x 100
[0122] (Maleic anhydride unit content in methacrylic copolymer) The IR spectrum of the methacrylic copolymer obtained in the examples was measured at room temperature using a Nicolet iN10MX made by ThermoScientific Corporation. -1 The absorption intensity of the peak due to the carbonyl of maleic anhydride in the vicinity and 1685 cm -1 The imidization rate of maleic anhydride (Im'; mol %) was calculated from the absorption intensity of the nearby peak derived from the carbonyl of maleimide. 13The amount of maleic anhydride units (m; mass%) in the precursor polymer obtained by C-NMR and the imidization rate were calculated using the following formula to determine the amount of maleic anhydride units (R- m % by mass. Maleic anhydride unit amount (R- m )=m×(100-Im'´) / 100
[0123] (Surface hardness) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the acrylic resin compositions obtained in the Examples and Comparative Examples were injection molded under conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec to obtain square test pieces with a thickness of 3 mm and a side length of 50 mm. In addition, using a single-screw extruder with a shaft diameter of 20 m, the acrylic resin compositions obtained in the Examples and Comparative Examples were extruded from a T-die with a width of 150 mm at a resin temperature of 260°C to obtain a single-layer film with a width of 100 mm and a thickness of 80 μm. The pencil hardness of each test piece and single layer film was measured under a load of 0.75 kg in accordance with JIS K5600-5-4. ○: Pencil hardness of test specimen and single layer film is H or higher ×: Pencil hardness of test piece or single layer film is F or less
[0124] (Photoelastic Coefficient) A 1.0 mm sheet was obtained by press molding a methacrylic copolymer. A 15 mm x 60 mm test piece was cut out from the center of the obtained press molded sheet. Both ends of the long side direction of the cut out sheet were fixed so that the distance between the chucks was 45 mm, and tension was applied to the sheet in steps of 10 N from 0 N to 100 N using an X-axis dovetail stage B05-11BM manufactured by Suruga Seiki. The tension T was monitored by a sensor separate type digital force gauge ZPS-DPU-50N manufactured by Imada Co., Ltd. The phase difference PD at each tension was measured at the D line wavelength of Na using KOBRA-WR manufactured by Oji Scientific Instruments. After the phase difference measurement, the sheet was removed from the jig and the thickness d of the phase difference measurement part was measured. From the measured values, the cross-sectional area S of the sheet (S = 15 mm × d), stress σ (= T / S), and birefringence Δn (= PD / d) were calculated, and the stress σ was plotted on the horizontal axis and the birefringence Δn on the vertical axis. The slope of the straight line obtained by the least squares method was taken as the photoelastic coefficient.
[0125] (Orientation birefringence) A 1.0 mm sheet was obtained by press molding the methacrylic copolymer. A 20 mm x 40 mm test piece was cut out from the center of the obtained press molded sheet, and the test piece was placed in an autograph with a heating chamber (manufactured by SHIMADZU). The grip distance in the autograph was set to 20 mm, and the sheet was held at the glass transition temperature + 10 ° C for 3 minutes. Then, the sheet was stretched 100% in one direction at a speed of 3 mm / min (grip distance became 40 mm). The obtained stretched film was cooled to 23 ° C, removed from the autograph, and the retardation PD of the central part of the stretched film was measured at the D line wavelength of Na using KOBRA-WR manufactured by Oji Scientific Instruments. The thickness d of the retardation measurement part was measured. From the measured value, the birefringence Δn (= PD / d) was calculated, and this was taken as the orientation birefringence.
[0126] Manufacturing Example 1 Purified methyl methacrylate (MMA), α-methylstyrene, maleic anhydride, 2,2'-azobis(2-methylpropionitrile) (AIBN), and n-octyl mercaptan (n-OM) were charged in the proportions shown in Table 1 into autoclave A equipped with a stirrer and dissolved uniformly to obtain polymerization raw materials.
[0127] The polymerization raw material was continuously supplied from the autoclave A at 1.5 kg / hr to a tank reactor controlled at a polymerization temperature of 120°C, and polymerization reaction was carried out by a bulk polymerization method with an average residence time of 2.5 hours, and a liquid containing a methacrylic copolymer was continuously discharged from the tank reactor. The polymerization conversion rate was the value shown in Table 1. Next, the liquid discharged from the reactor was heated to 230°C and supplied to a twin-screw extruder controlled at 240°C. In the twin-screw extruder, volatile matters mainly composed of unreacted monomers were separated and removed, and the methacrylic copolymer was extruded into strands. The strands were cut with a pelletizer to obtain a precursor polymer Aa. The weight average molecular weight Mw, each unit composition of the copolymer, and the glass transition temperature Tg of the obtained precursor polymer Aa were measured. The results are shown in Table 1. In this production example, the amount of units derived from MMA is the amount of units other than α-methylstyrene units, styrene units, and maleic anhydride units, so they are not listed in the table.
[0128] [Table 1]
[0129] Manufacturing Examples 2 to 7 Precursor polymers Ab to Ag were obtained in the same manner as in Production Example 1, except that the monomer composition in the polymerization raw materials and the amount of the chain transfer agent used were changed as shown in Table 1.
[0130] Production Example 8 An MS resin (a copolymer of methyl methacrylate (MMA) and styrene (St)) was produced according to the method for producing copolymer (A) described in the section [Examples] of JP 2003-231785 A. By changing the mass ratio of MMA, St, and t-dodecyl mercaptan (t-DM) charged in an autoclave, a precursor polymer Ah was obtained with Mw=95000, Tg=113°C, and a styrene monomer unit content of 20% by mass.
[0131] <Example 1> The precursor polymer [Aa] shown in Production Example 1 was fed at 2 kg / hr to the feed section of a twin-screw extruder (manufactured by Technobel Co., Ltd.; product name KZW20TW-45MG-NH-600) consisting of a feed section, a melt-kneading section, a devolatilizing section, and a discharge section, and set at a screw speed of 120 rpm and a temperature of 280° C., and monomethylamine was injected at 0.41 kg / hr from the additive feed port of the twin-screw extruder in the melt-kneading section equipped with a kneading block, to react the precursor polymer [Aa] with monomethylamine. A reverse flight was installed on the screw at the end of the reaction zone.
[0132] In the volatilizing section set at 20 Torr (about 2.7 kPa), by-products and excess monomethylamine were volatilized from the molten resin that had passed through the melt-kneading section, and discharged through a vent.
[0133] The molten resin extruded as a strand from a die provided at the end of the discharge section of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped methacrylic copolymer (Aa-1).
[0134] The copolymer (Aa-1) was fed at 1 kg / hr to the transport section of a twin-screw extruder (manufactured by Technobel Co., Ltd.; product name KZW20TW-45MG-NH-600) consisting of a transport section, a melt-kneading section, a devolatilizing section and a discharge section, and set at a screw speed of 100 rpm and a temperature of 280 ° C. In the melt-kneading section in which a kneading block was installed, a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.112 kg / hr, and the dimethyl carbonate was reacted with the carboxyl group in the methacrylic copolymer (Aa-1). A reverse flight was installed on the screw at the end of the reaction zone.
[0135] In the volatilizing section set at 20 Torr (about 2.7 kPa), by-products and excess dimethyl carbonate were volatilized from the molten resin that had passed through the melt-kneading section, and were discharged through a vent.
[0136] The molten resin extruded as a strand from a die provided at the end of the discharge section of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped methacrylic copolymer (Aa-2).
[0137] The methacrylic copolymer (Aa-2) was supplied at 1 kg / hr to the transport section of a twin-screw extruder (manufactured by Technobel Co., Ltd.; product name KZW20TW-45MG-NH-600), which consisted of a transport section, a melt-kneading section, a devolatilization section, and a discharge section, and was set at a screw rotation speed of 100 rpm and a temperature of 280°C.
[0138] In the volatilizing section set at 20 Torr (approximately 2.7 kPa), volatile matters such as unreacted substances were volatilized from the molten resin that had passed through the melt-kneading section, and discharged through a vent.
[0139] The molten resin extruded as a strand from a die at the end of the discharge section of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped methacrylic copolymer (A-1). The methacrylic copolymer (A-1) had an imidization rate Im of 62 wt%, a maleic anhydride unit amount M of 0 wt%, a glass transition temperature of 186°C, and an orientation birefringence of 0.10 x 10 -4 , the photoelastic coefficient is 0.21×10 -12 Pa -1 The physical properties of the methacrylic copolymer (A-1) are shown in Table 2.
[0140] <Example 2> A methacrylic copolymer (A-2) was obtained in the same manner as in Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ab), the amount of monomethylamine added was 0.29 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.077 kg / hr. The physical properties of the methacrylic copolymer (A-2) are shown in Table 2.
[0141] <Example 3> A methacrylic copolymer (A-3) was obtained in the same manner as in Example 1, except that the precursor polymer (Ac) was used instead of the precursor polymer (Aa), the amount of monomethylamine added was 0.32 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.086 kg / hr. The physical properties of the methacrylic copolymer (A-3) are shown in Table 2.
[0142] <Example 4> A methacrylic copolymer (A-4) was obtained in the same manner as in Example 1, except that the precursor polymer (Ad) was used instead of the precursor polymer (Aa), the amount of monomethylamine added was 0.38 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.103 kg / hr. The physical properties of the methacrylic copolymer (A-4) are shown in Table 2.
[0143] <Example 5> A methacrylic copolymer (A-5) was obtained in the same manner as in Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ae), the amount of monomethylamine added was 0.33 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.088 kg / hr. The physical properties of the methacrylic copolymer (A-5) are shown in Table 2.
[0144] <Comparative Example 1> A methacrylic copolymer (A-6) was obtained in the same manner as in Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Af), the temperature of the twin-screw extruder was set to 250°C, and the amount of monomethylamine added was 0.03 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.009 kg / hr. The physical properties of the methacrylic copolymer (A-6) are shown in Table 2.
[0145] <Comparative Example 2> A methacrylic copolymer (A-7) was obtained in the same manner as in Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ag), the temperature of the twin-screw extruder was set to 250°C, the amount of monomethylamine added was 0.15 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.04 kg / hr. The physical properties of the methacrylic copolymer (A-7) are shown in Table 2.
[0146] <Comparative Example 3> A methacrylic copolymer (A-8) was obtained in the same manner as in Example 1, except that the precursor polymer (Aa) was replaced with the precursor polymer (Ah), the temperature of the twin-screw extruder was set to 250°C, the amount of monomethylamine added was 0.26 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.07 kg / hr. The physical properties of the methacrylic copolymer (A-8) are shown in Table 2.
[0147] <Comparative Example 4> An acrylic copolymer (A-9) was obtained in the same manner as in Example 1, except that the precursor polymer [Aa] was used, no additives were added, and the copolymer was passed through the extruder without any additives. The physical properties of the acrylic copolymer (A-9) are shown in Table 2.
[0148] [Table 2]
[0149] The methacrylic polymers obtained in Examples 1 to 5 have high heat resistance, high optical isotropy (very small orientation birefringence and very small photoelastic coefficient), and high surface hardness, and therefore can be suitably used as materials for constituting optical members. On the other hand, the methacrylic copolymers obtained in Comparative Examples 1 to 4 are not within the scope of the present invention, and therefore have low optical isotropy or low surface hardness, and are therefore inferior to the present invention.
Claims
1. The polymer contains a structural unit (R) having at least one ring structure selected from the group consisting of methyl methacrylate units, α-methylstyrene units, maleic anhydride units, and the following formulae (1) to (3) in its main chain, and has an absolute photoelastic coefficient of 3.0×10 -12 P -1 and the absolute value of orientation birefringence of a stretched film obtained by stretching a 20 mm × 40 mm × 1.0 mm sheet in one direction by 100% at a speed of 3 mm / min at a temperature 10° C. higher than the glass transition temperature is 2.5×10 or less. -4 The following is a methacrylic copolymer: 【Chemistry 1】 (In formula (1), R 11 and R 12 are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. 【Chemistry 2】 (In formula (2), R 21 and R 22 are each independently a hydrogen atom or a methyl group; R 23 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. 【Chemistry 3】 (In formula (3), R 31 and R 32 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms; R 33 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.
2. The methacrylic copolymer according to claim 1, wherein the structural unit (R) is at least one structural unit selected from the group consisting of an N-substituted or unsubstituted glutarimide unit represented by formula (2) or an N-substituted or unsubstituted maleimide unit represented by formula (3).
3. The methacrylic copolymer according to claim 1 or 2, which has a glass transition temperature of 120° C. or higher.
4. The methacrylic copolymer according to any one of claims 1 to 3, comprising 22 to 87% by mass of methyl methacrylate units, 7 to 30% by mass of α-methylstyrene units, 1 to 30% by mass of maleic anhydride units, and 3 to 70% by mass of structural units (R).
5. The methacrylic copolymer according to any one of claims 1 to 4, which contains 0 to 30 mass% of other copolymerizable vinyl monomer units.
6. The methacrylic copolymer according to any one of claims 1 to 5, wherein the other copolymerizable vinyl monomer unit is at least one structural unit selected from the group consisting of an acrylic acid alkyl ester unit, an aromatic vinyl unit other than α-methylstyrene, and a vinyl cyanide unit.
7. A resin composition comprising the methacrylic copolymer according to any one of claims 1 to 6.
8. A molded article comprising the methacrylic copolymer according to any one of claims 1 to 6 or the composition according to claim 7.
9. The molded article according to claim 8 , wherein the molded article is a film or a sheet.
10. A method for producing a film or sheet, comprising a step of forming the methacrylic copolymer according to any one of claims 1 to 6 or the composition according to claim 7 into a film or sheet by a melt molding method.
11. A method for producing a film or sheet, comprising a step of forming the methacrylic copolymer according to any one of claims 1 to 6 or the composition according to claim 7 into a film or sheet by a solution casting method.
12. A laminate having at least one layer made of a film or sheet containing the methacrylic copolymer according to any one of claims 1 to 6 or the composition according to claim 7.
Citation Information
Patent Citations
Acrylic resin composition and optical film containing the same
JP2012518052A
Optical resin composition, and film
WO2015079693A1
Non-birefringent optical plastic material and optical member
JP2006308682A
Imide resin, resin composition for optical use, using the same, and molded article
JP2006328330A
Imide resin, and production method and use thereof
WO2005054311A1